Rational use of antibiotics during COVID-19 in Peru: Role of antimicrobial stewardship programs and interventions from the point of view of infection control - Pérez-Lazo, G (2021)
Antimicrobial resistance (AMR) is an additional slow-evolving pandemic that precedes the COVID-19 pandemic and will continue when it ends. However, in countries such as Peru where there is high consumption and inadequate prescription of antibiotics, a more challenging future scenario can be expected. Antimicrobial Stewardship Programs (ASP) are multidisciplinary teams of professionals that aim to contain the emergence of multidrug-resistant organisms through strategies such as audit of antibiotic prescription or creating antibiotic treatment guidelines based on local AMR rates. The difficulty in the timely diagnosis of co-infections or superinfections in the clinical course of COVID-19 leads to inappropriate use of antibiotics, forcing ASP to adapt their strategies in this changing scenario. In Latin America, ASP not only has to promote behavior change in antibiotic prescribers but also fight the epidemic of false information (infodemia) and disinformation campaigns on COVID-19. Furthermore, poor-quality infection prevention and control principles require evaluating strategies to mitigate the subsequent impact on the AMR.